Blink-related EEG oscillations are neurophysiological indicators of subconcussive head impacts in female soccer players: a preliminary study - Sattari, Sahar; Kenny, Rebecca; Liu, Careesa Chang; Hajra, Sujoy Ghosh; Dumont, Guy A.; Virji-Babul, Naznin (Frontiers in Human Neuroscience, 2023)
Repetitive subconcussive head impacts can lead to subtle neural changes and functional consequences on brain health. The objective assessment of these changes, however, is limited. Resting state blink-related oscillations (BROs), which are recently discovered neurological responses following spontaneous blinking, are explored in this first study to evaluate changes in BRO responses in subconcussive head impacts. We collected five-minute resting-state EEG data from two cohorts of collegiate athletes who were engaged in contact sports (SC) or non-contact sports (HC). Video recordings of all on-field activities were conducted to determine the number of head impacts during games and practices in the SC group. In both groups, we were able to detect a BRO response. Follwing one season of games and practice, we found a strong association between the number of head impacts sustained by the SC group as well as increases in delta and beta spectral power post-blink. A significant difference was also observed between the two groups in the morphology of BRO responses including decreased peak-to-peak amplitude of response over left parietal channels and differences in spectral power in delta and alpha frequency range post-blink. Our preliminary results suggest that the BRO response may be a useful biomarker for the detection of subtle neural changes resulting from repetitive head impacts. The clinical utility of this biomarker will need to be validated through further research with larger sample sizes with both males and females participants using a longitudinal design.